Analisis Aspek Keperilakuan Dalam Proses Penganggaran di Perbankan Syariah - Alan Januar Ahmed; Masiyah Masiyah; Ahmad Juanda (Jurnal Ekonomi Manajemen Perbankan, 2025)
This study analyzes behavioral aspects of the budgeting process in Indonesian Islamic banking with a focus on factors that influence the effectiveness of the budgeting system and dysfunctional employee behavior. Using a quantitative approach with a survey method on 456 respondents involved in the budgeting process in Indonesian Islamic banks, this study examines the influence of budget participation, perceptions of fairness, Islamic leadership style, Islamic organizational culture, and sharia commitment on budgeting effectiveness and dysfunctional behavior. Data analysis using Structural Equation Modeling (SEM) with PLS-SEM resulted in findings that all independent variables have a significant positive effect on budgeting effectiveness, with Islamic leadership style showing the strongest influence (β = 0.312), followed by sharia commitment (β = 0.289), budget participation (β = 0.247), Islamic organizational culture (β = 0.203), and perceptions of fairness (β = 0.186). All variables were also shown to have a significant negative effect on dysfunctional behavior, with sharia commitment having the strongest negative effect (β = -0.315). The level of sharia education and work experience were shown to moderate this relationship. The results of this study demonstrate the importance of integrating Islamic values ​​into the budgeting system to improve organizational effectiveness and reduce dysfunctional practices, providing a theoretical contribution to the sharia financial management literature and practical guidance for sharia banking managers in optimizing a budgeting system based on Islamic values.